Hollywood remembered : an oral history of its golden age - Zollo, Paul, 1958- (New York : Cooper Square Press ; [S.l.] : Distributed by National Book Network, 2002)
A collection of thirty-seven reminiscences in which actors, directors, cinematographers, agents, studio executives, and screenwriters trace the history of Hollywood from the turn of the twentieth century to the present.
Includes bibliographical references (p. [362]) and index.
Library Journal, November 2002
Publisher's Weekly, October 2002
Kirkus Starred, September 2002
Adult
Keywords: Motion picture industry -- Los Angeles (Calif.) -- History; Motion pictures -- Los Angeles (Calif.) -- Biography